Pathological and Immunohistochemical Characterization of Follicular Gastritis (Gastric Lymphofollicular Hyperplasia) in 41 Dogs - Andrada Negoescu; Corina Toma; Claudiu Gal; Constantin Ifteme; Bianca Bofan; Teodoru Soare; Irina Amorim; Raluca Maria Pop; Ştefan Cristian Vesa; Dragoș Hodor; Elvira Gagniuc; Cornel Cătoi; et al. (Animals)
Gastric lymphofollicular hyperplasia (GLFH) is characterized by large lymphoid nodules in the lamina propria. Its etiology and immunohistochemical characteristics are poorly understood. This study analyzed 41 canine GLFH cases, including clinical, endoscopic, histopathological, and immunohistochemical evaluations. Young French Bulldogs (75.06%) were the most affected. Endoscopically, lymphoid nodules were identified in both the antrum and gastric body. Lymphoid follicle diameters were similar in the gastric body (mean 295.587 μm) and antrum (mean 294.641 μm). Associated lesions included glandular atrophy, lymphoplasmacytic inflammation, and fibrosis. Minimal, moderate, and severe colonization with Helicobacter-like organisms (HLOs) were observed in 20, 6, and 3 cases, respectively. B-cell lymphocytes positive for Bcl6 and Pax5 were localized centrally in large follicles, surrounded by CD3+ T lymphocytes. Small follicles lacked germinal centers and showed mixed T and B lymphocytes. A positive correlation was found between the follicle diameter and both HLOs colonization (p = 0.049) and follicular hyperplasia (p < 0.001). A regression analysis indicated that HLOs colonization and hyperplasia accounted for 42.3% of follicle diameter variance (R2 = 0.423, p < 0.001). Additional studies are required to investigate potential correlations between GLFH and HLOs, as well as to assess the role of this lesion in the progression to neoplasia.